2017
DOI: 10.1063/1.4987012
|View full text |Cite
|
Sign up to set email alerts
|

In silico screening of drug-membrane thermodynamics reveals linear relations between bulk partitioning and the potential of mean force

Abstract: The partitioning of small molecules in cell membranes-a key parameter for pharmaceutical applicationstypically relies on experimentally-available bulk partitioning coefficients. Computer simulations provide a structural resolution of the insertion thermodynamics via the potential of mean force, but require significant sampling at the atomistic level. Here, we introduce high-throughput coarse-grained molecular dynamics simulations to screen thermodynamic properties. This application of physics-based models in a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(79 citation statements)
references
References 43 publications
2
76
0
Order By: Relevance
“…Menichetti et al recently demonstrated this by running Martini HTCG simulations to construct a structure-property relationship describing the thermodynamics of the insertion of a small organic molecule into a biological membrane across CCS. 28,29 In doing so, they discovered a linear relationship between the bulk partitioning behavior of the solute and its potential of mean force. They were then able to identify a structure-property hyper surface to obtain membrane permeabilities for these solute molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Menichetti et al recently demonstrated this by running Martini HTCG simulations to construct a structure-property relationship describing the thermodynamics of the insertion of a small organic molecule into a biological membrane across CCS. 28,29 In doing so, they discovered a linear relationship between the bulk partitioning behavior of the solute and its potential of mean force. They were then able to identify a structure-property hyper surface to obtain membrane permeabilities for these solute molecules.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown in the previous section that the strength of phase separation, expressed by f mix , correlates well with the dimer's relative partitioning between different lipid environments, quantified by the transfer free energy, ∆∆G. As such, using PMFs in the three lipid environments representative of Lo-Ld equilibrium offers two advantages: (i) identify the preferred lipid environment and (ii) estimate the dimer-induced effects on phase separation, both at a reduce computational cost (29)(30)(31). Additionally, the PMF profile contains spatial information about the insertion, which we have observed to also play a role in determining the bilayer-modifying character of the solute.…”
Section: High-throughput Search For Phase-modifying Solutesmentioning
confidence: 91%
“…Rather than focusing on specific compounds, we considered all CG dimers by exhaustively enumerating all combinations of neutral Martini beads. This resulted in a total of 105 dimer solutes, covering a wide range of hydrophobicity (29,30). Hence, a US simulation was constructed for each combination of solute and membrane environment, using as reaction coordinate the distance along the bilayer normal, z, between the membrane midplane and the solute molecule.…”
Section: Umbrella Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the recently established PerMM database (10) covers only cellular permeability together with permeability prediction using an implicit membrane model with rigid compounds. Finally, molecular dynamics simulations are often used for predictions of membrane partitioning (11) or permeability even on a large scale (12,13). However, current theoretical predictions of molecule/membrane interactions vary by method as well as in comparison with data from experiments, lacking community benchmark comparison between individual methods.…”
Section: Introductionmentioning
confidence: 99%